Częstochowskie szkoły muzyczne w okresie dwudziestolecia międzywojennego. Zarys problematyki - Wrona-Meryk, Izabela (Biuletyn Historii Wychowania, 2026)
The situation of music education in the 19th century was very difficult. Most people interested in this field studied under the supervision of private teachers. The education usually included playing a chosen instrument, without additional subjects in the field of music theory. The level of private teachers varied greatly. There were both professionals and amateurs among them. In Czestochowa, changes began to occur gradually with the establishment of the first professional music school established by Ludwik Wawrzynowicz, two private ones headed by Feliks Witeszczak and Bolesław Grzewiński, and other associations operating in the craft and industrial environment. Thanks to them, the group of professional musicians, performers, teachers, popularizers and music activists grew. The article presents an outline of the activities of the above-mentioned music schools operating in the city during the interwar period.